Importance of resilience for the multidisciplinary team (Research, Society and Development, 2021)
Resilience is an essential factor for health professionals to successfully perform their functions. The aim of the study was to understand the institutional and neurophysiological mechanisms that help health professionals in promoting resilience. This is a systematic review carried out from research with the descriptors "Patient Care Team", "Neurophysiology" and "Psychological Resilience", combined with the Boolean descriptor "AND", in the databases BVS, SciELO, PubMed and Portal de Periódicos CAPES, 3,047 articles were found. The inclusion criteria of the defined articles were: texts available online, in full and free of charge, in Portuguese, English and Spanish, published between the years 2014 to 2020. After applying the inclusion and exclusion criteria, 1,082 remained, when reading of the title and abstract, only 73 studies were selected for full reading, of which 10 were chosen to compose the database of this review. The resilience among health professionals who work in the emergency room is lower than that of other specialties. Several studies have identified the protective role of personal resilience during disaster events and disease outbreaks, suggesting that strengthening resistance levels and coping skills can help them manage and deal with stressful situations effectively. Resilience is relevant for health professionals, as it improves the professional's performance in the work environment and helps in coping with various stressful situations. Given this, we realized the need to implement measures that promote the development of resilience for these individuals.